Urbanization and administrative restructuring: A case study on the Wuhan urban agglomeration. (July 2016) - Zeng, Chen; Zhang, Anlu; Xu, Shan
Abstract: Urbanization in China has been closely associated with urban sprawl, rural migration and the role of government has been more direct and powerful in setting it in motion. In 2014, the New Urbanization Planning in China has been released in which the development of urban agglomeration and small-medium cities has been highlighted. In this context, we decompose urbanization into population-oriented and land-centered archetypes and devise spatial models in multiple strategies embedded with different spatial relations to unfold the underlying driving forces using Wuhan agglomeration as the case. In addition to the identification of major driving forces which are gross domestic product (GDP), income, fixed asset investment and the transportation construction, the major contributions of our study lie in the gauge on administrative influence, to be more specific, the status of urban district, city-level county and county, through incorporating different spatial weight matrix in different scenarios in spatial modeling. It found out that 1) both non-agricultural population and urban land exhibit significant spatial autocorrelation and the superiority in the city center is evident; 2) socio-economic development and transportation construction significantly influence urbanization whereas the personal income and fixed asset investment accounting for a large proportion being the most powerful factors; 3) different administrative status at the county level is an unneglectable factor and urban area has higher probability to expand when urban district is adjacent to county-level city; 4) the magnitude of this administrative status influence generally grows to a certain level and then reaches to a plateau. These findings provide theoretical basis for understanding the administrative dimension in new urbanization and have important policy implications on administrative adjustment and urban agglomeration. Highlights: We decompose urbanization into population-oriented and land-centered archetypes to unfold the underlying driving forces. We incorporate three different administrative status into spatial weight matrix to measure the administrative influence. Socio-economic development and transportation construction significantly influence urbanization in Wuhan agglomeration. The spatial interaction is more powerful when county-level city is adjacent to urban district in land-dominated urbanization.